Simulakra dan Hiperrealitas dalam Rekrutmen Para Pengantin ISIS (Islamic State of Iraq and Syria) - Pratiwi, Vandita Oktavia; Pattipeilhy, Shary Charlotte Henriette (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2021)
The phenomenon of an ISIS (Islamic State in Iraq and Syria) bride who was recruited by a Middle Eastern jihadist group and was banished by her country of origin caused controversy after the confession of the spread of false realities in her recruitment. The refusal of recognition as citizens for former members occurs because of an incident that betrays and is imposed by the state. In this case, ISIS does not only recruit men, but women are also often recruited by ISIS to become jihadist brides as a form of its jihad by using online media to implement a false reality. This research uses Post-Structuralism theory with its derivative concept, namely Simulakra by Jean Baudrillard. The author collects data using the literature study method through journals/articles, books, websites, international news, films, and interviews with several sources. The research is descriptive and explanatory, which will provide an overview of the reasons why women joined ISIS as jihadi brides, how the form of the strategy used by ISIS in implementing false realities, and also explain why ISIS chose this strategy. The result of this research is that the role of online media (social and mass) is very effective in working groups so many women are interested in joining it on the grounds that it is a form of migration and lives under the auspices of the chaliphate.